Characterization of Uncultured Genome Fragment from Soil Metagenomic Library Exposed Rare Mismatch of Internal Tetranucleotide Frequency - Liu, Yunpeng; Yang, Dongqing; Zhang, Nan; Chen, Lin; Cui, Zhongli; Shen, Qirong; Zhang, Ruifu (Frontiers in Microbiology, 2016)
Exploring the genomic information of a specific uncultured soil bacterium is vital to understand its function in the ecosystem but is still a challenge due to the lack of culture techniques. To examine the genomes of uncultured bacteria, a metagenomic bacterial artificial chromosome (BAC) library derived from a soil sample was screened for 16S rDNA-containing clones. Five clones (4C6, 5E7, 5G4, 5G12, 5H7) containing uncultured soil bacteria genome fragment (with low 16S rDNA similarity to isolated bacteria) were selected for sequencing. Clone 5E7 and 5G4 showed only 82% and 83% of 16S rDNA identity to known sequences. Phylogenetic analysis of 16S rDNA indicated that 5E7 and 5G4 were potentially from new class of Chloroflexi. Only one-third of the 5G4 ORFs have significant hits against HMMER. Internal tetranucleotide frequency analysis indicated that the unknown region of 5G4 was poorly correlated with other parts of the clone, indicating that this section might be obtained through lateral transfer. It was suggested that this region rich for unknown genes is under fast evolution.